Kepentingan Nasional Indonesia dalam Inisiasi ASEAN Maritime Forum (AMF) - Najamuddin Khairur Rijal (Universitas Diponegoro, 2018)
The complexity of maritime security issues and problems in Southeast Asia became attention of ASEAN states which further encouraged the formation of the ASEAN Maritime Forum (AMF). AMF is a concept and proposal submitted by Indonesia and became one of the ASEAN Political-Security Community points. This research examines Indonesia’s national interest in establishment of AMF. Based on national interest concept, there are three Indonesia’s interest as focus of this study. First, Indonesia’s interest as an Archipelago States and has a history of maritime glories. Second, maritime as sovereignty and the AMF existence as Indonesia efforts to maintaining maritime territorial integrity. Third, maritime economic as the third Indonesia’s interests in propose of AMF establishment. In addition, this study also examine how the achievement of the Indonesia’s national interests in AMF.Keywords: AMF, archipelago states, Indonesia, national interest